A nationwide evaluation of off-label drug utilization in Turkey - (:unkn) unknown (My University, 2017)
0

Background/aim: Off-label drug use (OLDU) is under the control of the Turkish Medicines and Medical Devices Agency (TMMDA) in Turkey. It was aimed to investigate demographic and medical features of patients with OLDU applications in Turkey. Materials and methods: A total of 4426 electronic OLDU application records of the TMMDA were evaluated retrospectively. Information regarding patients demographic characteristics, diagnoses, requested drugs, institutions, and specialties of the physicians were evaluated. Results: OLDU applications were mostly made by rheumatologists (21.5%) and 95.2% of them were approved by the TMMDA. The mean age of the patients was 35 years and 54.4% of them were female. Off-label drugs were mostly prescribed for patients aged 18 64 years (62.1%) and were most frequently prescribed by physicians from university medical centers (81.0%). Systemic lupus erythematosus (10.1%) was the most common diagnosis. Mycophenolate (16.1%) and rituximab (10.1%) were the most frequently prescribed off-label drugs. There were differences regarding some characteristics of patients and their physicians among most frequently prescribed off-label drugs (P < 0.05). Conclusion: It is noteworthy that OLDU applications showed demographical and institutional differences. It is expected that this study will provide important contributions to physicians working in the relevant area with respect to treatment alternatives of diseases with treatment challenges.
Keywords: Cerrahi